The Trilogy of Islamic Epistemology: Integrating Bayani, 'Irfani, and Burhani in Modern Islamic Educational Research - Fikri Al Ghifar; Maspuroh; Natasya Ramadina Azura; Syifa Alawiyah; Hudallah (Lentera Peradaban: Journal on Islamic Studies, 2025)
Epistemology within the Islamic educational tradition serves as a critical philosophical anchor for understanding the nature, acquisition, and sources of knowledge. This paper examines the "Trilogy of Islamic Epistemology"—comprising Bayani (text-based), 'Irfani (intuitive/gnostic), and Burhani (rational/demonstrative)—which uniquely defines the intellectual landscape of Muslim scholarship. Unlike secular educational models, Islamic educational thought integrates these three dimensions to form a holistic worldview. By employing a multi-faceted methodology—including deduction, induction, and consultation—this study traces how these epistemological roots contribute to the treasury of Islamic pedagogical theory. The findings suggest that the synergy between these dimensions provides a robust framework for responding to contemporary educational challenges while maintaining authentic Islamic characteristics.